Clostridium Difficile Infection in Acute Care Hospitals: Systematic Review and Best Practices for Prevention. (16th March 2017) - Louh, Irene K.; Greendyke, William G.; Hermann, Emilia A.; Davidson, Karina W.; Falzon, Louise; Vawdrey, David K.; Shaffer, Jonathan A.; Calfee, David P.; Furuya, E. Yoko; Ting, Henry H.
Abstract : OBJECTIVE: Prevention of Clostridium difficile infection (CDI) in acute-care hospitals is a priority for hospitals and clinicians. We performed a qualitative systematic review to update the evidence on interventions to prevent CDI published since 2009. DESIGN: We searched Ovid, MEDLINE, EMBASE, The Cochrane Library, CINAHL, the ISI Web of Knowledge, and grey literature databases from January 1, 2009 to August 1, 2015. SETTING: We included studies performed in acute-care hospitals. PATIENTS OR PARTICIPANTS: We included studies conducted on hospitalized patients that investigated the impact of specific interventions on CDI rates. INTERVENTIONS: We used the QI-Minimum Quality Criteria Set (QI-MQCS) to assess the quality of included studies. Interventions were grouped thematically: environmental disinfection, antimicrobial stewardship, hand hygiene, chlorhexidine bathing, probiotics, bundled approaches, and others. A meta-analysis was performed when possible. RESULTS: Of 3, 236 articles screened, 261 met the criteria for full-text review and 46 studies were ultimately included. The average quality rating was 82% according to the QI-MQCS. The most effective interventions, resulting in a 45% to 85% reduction in CDI, included daily to twice daily disinfection of high-touch surfaces (including bed rails) and terminal cleaning of patient rooms with chlorine-based products. Bundled interventions and antimicrobial stewardship showed promise for reducing CDI rates. Chlorhexidine bathing and intensified hand-hygiene practices were not effective for reducing CDI rates. CONCLUSIONS: Daily and terminal cleaning of patient rooms using chlorine-based products were most effective in reducing CDI rates in hospitals. Further studies are needed to identify the components of bundled interventions that reduce CDI rates. Infect Control Hosp Epidemiol 2017;38:476–482